2017
DOI: 10.1007/s11842-017-9379-9
|View full text |Cite
|
Sign up to set email alerts
|

Social Values of Forests and Production of New Goods and Services: The Views of Swedish Family Forest Owners

Abstract: Forests are considered crucial assets for sustainable rural development, and contemporary forestry is an industry where production, environmental and social goals can-and should-be handled simultaneously. Swedish family forest owners (FFOs) are expected to both manage and conserve their forests for the benefit of the whole country, but there are contradictions between development and conservation and between traditional and alternative forms of utilization representing dilemmas in rural areas. Tensions between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 36 publications
0
19
1
2
Order By: Relevance
“…Within the framework of social functions, special forest parking facilities, forest education centres as well as cycling, horse-riding and walking trails are established to ensure safe and organised opportunities to use the forest value. Moreover, forestry is an important element in rural development, as it has been indicated by several authors, for example, Adamowicz (2005Adamowicz ( , 2008, Szramka (2005Szramka ( , 2006Szramka ( , 2008, Liu et al (2018), Pereira and Martinho (2017) and Bjarstig and Stens (2018). The forest offers jobs to the local residents, primarily in rural areas.…”
Section: Discussionmentioning
confidence: 95%
“…Within the framework of social functions, special forest parking facilities, forest education centres as well as cycling, horse-riding and walking trails are established to ensure safe and organised opportunities to use the forest value. Moreover, forestry is an important element in rural development, as it has been indicated by several authors, for example, Adamowicz (2005Adamowicz ( , 2008, Szramka (2005Szramka ( , 2006Szramka ( , 2008, Liu et al (2018), Pereira and Martinho (2017) and Bjarstig and Stens (2018). The forest offers jobs to the local residents, primarily in rural areas.…”
Section: Discussionmentioning
confidence: 95%
“…Instead, Swedish forest policy explicitly affirms the importance of "freedom with responsibility," granting all Swedish forest owners, public and private, large-scale and small-scale, substantial scope to decide how to incorporate environmental protection in the management of their forests Keskitalo 2014, Beland Lindahl et al 2017). Previous research has shown that forest owners have multiple objectives, suggesting that an emphasis on only economic benefits is not desirable from the forest owners' point of view (Bjärstig and Sténs 2018). However, a recent study of Swedish forest policy has found that the current governance model adapts a "more-of-everything" pathway, in which various ecological, economic, and social goals are expected to be prioritized and achieved simultaneously (Beland Lindahl et al 2017).…”
Section: Case Study and Methodsmentioning
confidence: 99%
“…Bernard, N. Gélinas DOI: 10.4236/nr.2020.117017 285 Natural Resources cial). Bjärstig and Sténs [10] defined multifunctionality as an array of services and functions that are provided by the land for the benefit of the people and their environment. However, the forests are managed in order to respect the sustained yield doctrine, which has been described as "the 'holy grail' of foresters all over the world for more or less two centuries" ( [11], p. 7).…”
Section: Ilrm a Theoretical Conceptmentioning
confidence: 99%